Landuse impacts on water quality of the lake and river environment of Tasik Chini Pahang - Dom, N. M.; Ahmad, R.; Sulaiman, S.; Ibrahim, S. L.; Saadon, A; Zamri, Z; Nadiatul Adilah, Ahmad Abdul Ghani; Tholibon, D. A; Kamal, N. A; Ariffin, J (2018)
Tasik Chini has undergone considerable change in landuse at least in the last 10 years. Landuse activities have range from plantation, mining activities to settlements in the lake perimeter. Change in the landuse pattern will cause change in the hydrological system of the watershed that cause subsequent changes in the water quality of the lake as well as to the lake configuration. Sediment and other organic pollutants are expected to increase with subsequent increase in the surface runoff as a result of the change in landuse pattern. A study was carried out at Tasik Chini to evaluate the sediment load at Sungai Jemberau and Sungai Chini while the water quality parameters were measured on nine feeder rivers in several locations. Sungai Jemberau has been identified as the most critical river due to its close proximity to the mining area at Bukit Ketaya. Measurements on the suspended-sediment concentration and water quality were carried out during the wet months in November and December 2016. This study establishes the water quality index (WQ Index) and the probable cumulative total maximum daily load (TMDL) for 5, 10, 15 and 20 years for the study area.